Aneuploid acute myeloid leukemia exhibits a signature of genomic alterations in the cell cycle and protein degradation machinery. Issue 5 (27th November 2018) - Simonetti, Giorgia; Padella, Antonella; do Valle, Italo Farìa; Fontana, Maria Chiara; Fonzi, Eugenio; Bruno, Samantha; Baldazzi, Carmen; Guadagnuolo, Viviana; Manfrini, Marco; Ferrari, Anna; Paolini, Stefania; Papayannidis, Cristina; et al.
Abstract : Background: Aneuploidy occurs in more than 20% of acute myeloid leukemia (AML) cases and correlates with an adverse prognosis. Methods: To understand the molecular bases of aneuploid acute myeloid leukemia (A‐AML), this study examined the genomic profile in 42 A‐AML cases and 35 euploid acute myeloid leukemia (E‐AML) cases. Results: A‐AML was characterized by increased genomic complexity based on exonic variants (an average of 26 somatic mutations per sample vs 15 for E‐AML). The integration of exome, copy number, and gene expression data revealed alterations in genes involved in DNA repair (eg, SLX4IP, RINT1, HINT1, and ATR ) and the cell cycle (eg, MCM2, MCM4, MCM5, MCM7, MCM8, MCM10, UBE2C, USP37, CK2, CK3, CK4, BUB1B, NUSAP1, and E2F ) in A‐AML, which was associated with a 3‐gene signature defined by PLK1 and CDC20 upregulation and RAD50 downregulation and with structural or functional silencing of the p53 transcriptional program. Moreover, A‐AML was enriched for alterations in the protein ubiquitination and degradation pathway (eg, increased levels of UHRF1 and UBE2C and decreased UBA3 expression), response to reactive oxygen species, energy metabolism, and biosynthetic processes, which may help in facing the unbalanced protein load. E‐AML was associated with BCOR / BCORL1 mutations and HOX gene overexpression. Conclusions: These findings indicate that aneuploidy‐related and leukemia‐specific alterations cooperate to tolerate an abnormal chromosome number in AML, and they point to the mitotic and protein degradation machineries as potential therapeutic targets. Abstract : Aneuploid acute myeloid leukemia (A‐AML) is associated with genomic and transcriptional alterations in the cell cycle and protein degradation pathways. The upregulation of PLK1 and CDC20 and the downregulation of RAD50 and of a p53‐related signature are hallmarks of A‐AML.